Regulatory infrastructure for radiation protection and the safety of ionizing radiation sources in Mozambique (Brazilian Journal of Radiation Sciences (BJRS), 2024)
There has been a growing number of peaceful applications of ionizing radiation in Mozambique since 2006, when the country became a member state of the International Atomic Energy Agency, which was instrumental in assisting Mozambique with establishing its national ionizing radiation safety authority. Literary review was used to collect the data from publications of the International Atomic Energy Agency, and most of the non-published information was collected at the National Atomic Energy Agency and at the Faculty of Science of the Eduardo Mondlane University in Maputo, Mozambique. Seven aspects of the national regulatory infrastructure are described in this paper. The establishment of a national radiation safety authority has been successful and will ensure an acceptable safety standard protection of the people and environment from detrimental effects of ionizing radiation.